2021
DOI: 10.1021/acsomega.1c01675
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature and CO2 on High-Temperature Behavior and Microstructure of Metallurgical Coke

Abstract: Metallurgical coke is an important raw material for blast furnaces. Specifically, temperature and CO2 significantly affect its metallurgical behavior. In this study, the influence of temperature and CO2 on the high-temperature behavior of three metallurgical coke samples, used in blast furnaces of different volumes, was investigated. The carbon structure and pore structure of the coke samples were analyzed. The results indicated that as the temperature increased from 1100 to 1500 °C, the weight loss ratio incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Therefore, the quality of metallurgical coke is closely related to the technical and economic indicators of blast furnaces. Mansheng et al found that from 1100 °C to 1500 °C, the coke weight-loss ratio increased by 10-fold, and the drum strength decreased by 80%; in a CO 2 atmosphere, when the temperature increased from 1100 °C to 1300 °C, the coke reactivity increased by 50%, and the coke strength decreased after the reaction [ 13 ]. Zhongsuo used different methods to analyze the kinetics of carbon dioxide gasification of metallurgical coke, and proposed new kinetic equations and predicted kinetic curves [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the quality of metallurgical coke is closely related to the technical and economic indicators of blast furnaces. Mansheng et al found that from 1100 °C to 1500 °C, the coke weight-loss ratio increased by 10-fold, and the drum strength decreased by 80%; in a CO 2 atmosphere, when the temperature increased from 1100 °C to 1300 °C, the coke reactivity increased by 50%, and the coke strength decreased after the reaction [ 13 ]. Zhongsuo used different methods to analyze the kinetics of carbon dioxide gasification of metallurgical coke, and proposed new kinetic equations and predicted kinetic curves [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The carbon structure and pore characteristics of metallurgical coke have a significant impact on coke behavior and reactivity in a blast furnace. The basic unit of the carbon structure is a graphite crystallite, and the size of the graphite crystallite can usually be characterized by the stacking height Lc of the carbon substrate. , In this study, the stacking height Lc was calculated using Origin. First, the XRD data was drawn, and then the “multipeak fitting” was carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the microcrystalline structure of coke is an important factor affecting coke reactivity. 24 Figure 2 shows the XRD spectra of coke obtained from coal blends with different proportions of GL. The addition of GL weakens the peak intensities of 002 and 100, which represent the size and orientation of the carbon reticulum layer in the aromatic ring of coke, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The edge of the coke microcrystal belongs to the defect site of the crystal lattice, which can form unsaturated chemical bonds easily by combining heteroatoms, and becomes the active center during gasification reaction to promote the gasification activity. Therefore, the microcrystalline structure of coke is an important factor affecting coke reactivity Figure shows the XRD spectra of coke obtained from coal blends with different proportions of GL.…”
Section: Resultsmentioning
confidence: 99%